(3CSGSjGJ aj OQGSI GdEOGQI GdYGeIs - (3SYjO eMeO(B, (3GdeUQjs ((3GdQjGV(B:s (3OGQ GdeQjN(B,s, 2001)
(3GdeMJhjGJ (B: (3GdHGH GdChd (B: (3bVGjG heaGgje CSGSjI (B: (3GdeHMK GdChd (B: (3eaghe GdEOGQI GdYGeI hWHjYI efXGeJgG (B: (3GdeHMK GdKGfj (B: (3eaghe GdOhdI hGdMcheI(B-(3GdHGH GdKGfj (B: (3dUGdM GdYGe hefXeGJ GdCOGQI GdYGeI (B: (3GdeHMK GdChd (B: (3eaghe GdUGdM GdYGe (B: (3GdHGH GdKGdK (B: (3GdJfXje hCHYGOg GdQFjSjI aj eLGd GdEOGQI GdYGeI (B: (3GdeHMK GdChd (B: (3GdOQGSGJ GdJfXjejI heaghe GdfXe(B-(3GdHGH GdQGHY (B: (3GdHjQhbQGWjI hHfjFI GdEOGQI GdYGeI (B: (3GdeHMK GdChd (B: (3XGgQI GdHjQhbQGJWjI hGdEOGQI GdYGeI(B-(3GdHGH GdNGeS (B: (3GdJQcjHI GdHjFjI ddEOGQI GdYGeI (B: (3GdeHMK GdChd (B: (3YfGUQ GdHjFI hBKQgG Ydi GdEOGQI GdYGeI (B: (3GdeHMK GdKGfj (B: (3YfGUQ GdHjFI GdGbJUGOjI hBKQgG Ydi GdEOGQI GdYGeI(B-(3GdHGH GdSGOS (B: (3GdbjGOI hYedjI GJNGP GdbQGQGJ aj efXeGJ GdEOGQI GdYGeI (B: (3GdeHMK GdChd (B: (3YedjI GJNGP GdbQGQGJ hCHYGOgG aj efXeGJ GdEOGQI GdYGeI (B: (3GdeHMK GdKGfj (B: (3YedjI GdbjGOI hCHYGOgG aj efXeGJ GdCOGQI GdYGeIs
Keywords: (3GdEOGQI GdYGeIs